Mites (Acari) at the edges of bog pools in Orawa–Nowy-Targ Basin (S Poland), with particular reference to the Oribatida - Seniczak, Anna; Seniczak, Stanisław; Kowalski, Jarosław; Graczyk, Radomir; Mistrzak, Marcin (Biological Letters, 2015)
Mites, and among them especially the Oribatida, are very abundant in bogs, being good bioindicators of various changes, but little is known about their reaction to heavy industrial exploitation of bogs. This study aimed to compare the acarofauna of the edges of small pools located in 2 bogs of Orawa-Nowy-Targ Basin (Kotlina Orawsko-Nowotarska), namely Łysa Puścizna (LP) and Bór Podczerwony (BP), degraded to different degrees by peat exploitation. The area of bog LP has decreased since the end of the 19th century by 34%, while that of BP has decreased during this time drastically (by 68%). Water in both studied pools differed from that in natural bogs, reported in the literature, especially in pH, colour, and oxygen conditions (COD and BOD5), and these differences were more pronounced at BP. The abundance of mites was similar to that observed in natural bogs, and the Oribatida dominated among mites, constituting over 99% of them. The species diversity of Oribatida was low in both pools, but especially in pool BP. In both bogs the aquatic species were the most abundant due to the wet study season. The species structure of Oribatida differed, however, from that reported from natural bogs as well as from each other. At the less degraded bog LP the most abundant was Hydrozetes lacustris (D = 69%), while at bog BP, with worse water parameters, Trimalaconothrus maior highly dominated (D = 93%). This suggests that the latter species is very tolerant to water parameters, being a successful coloniser of degraded bogs.